The gut reaction to traumatic brain injury - Katzenberger, Rebeccah J (Fly (Austin), 2015)
Traumatic brain injury (TBI) is a complex disorder that affects millions of people worldwide. The complexity of TBI partly stems from the fact that injuries to the brain instigate non-neurological injuries to other organs such as the intestine. Additionally, genetic variation is thought to play a large role in determining the nature and severity of non-neurological injuries. We recently reported that TBI in flies, as in humans, increases permeability of the intestinal epithelial barrier resulting in hyperglycemia and a higher risk of death. Furthermore, we demonstrated that genetic variation in flies is also pertinent to the complexity of non-neurological injuries following TBI. The goals of this review are to place our findings in the context of what is known about TBI-induced intestinal permeability from studies of TBI patients and rodent TBI models and to draw attention to how studies of the fly TBI model can provide unique insights that may facilitate diagnosis and treatment of TBI.